Features of Social Reality Representation Through Phraseology in Media Discourse (Linguostylistic Studies, 2021)
The study of phraseology in media discourse focuses on the individual linguistic worldview of the author represented by lexical and phraseological means that reflect the uniqueness of the author’s vision of national-cultural traditions. The scientific research paradigm draws on the principles of anthropocentrism.The purpose of the research is to analyze the features of the common idioms and transformed phraseological units use as a stylistic device to reflect social reality and to determine their pragmatic potential in media discourse. The methods of descriptive, contextual-interpretive, and transformational analysis have been applied to achieve the research goals.In media discourse, stable and transformed phraseological units are active linguistic and expressive means of social reality representation. Among the methods of transformation, the most productive are contamination, substitution, and syncopation, which have the strongest effect on the addressee.The pragmatic potential of phraseology as a means of speech influence is revealed in the individual-authorial features of world perception, processing of the received information, and, accordingly, reaction to it. Journalists, politicians, researchers using a certain PhU demonstrate exactly their personal interpretation of the events. In media discourse, phraseology is used as a communicative strategy to achieve a specific goal.Further research is needed to analyze the linguistic and pragmatic, structural, and semantic aspects of the Ukrainian language phraseological units functioning in media discourse.
Keywords: phraseological unit; structural and semantic transformation; idiostyle